Risky sexual behavior in adolescents does not depend on the level of knowledge about HIV/AIDS? (Research, Society and Development, 2021)
Objective: to assess the knowledge and practices of adolescent students in relation to HIV/AIDS and other STIs. Methods: this is a cross-sectional study, with a quantitative approach, which included twelve public schools from seven cities in Rio Grande do Norte, with a sample of 623 individuals. Two electronic and interactive questionnaires were used for data collection. Data processing was performed using SPSS 25.0® and Stata 14.0. For the analysis of associated factors, the Item Response Theory was used. The project of this study was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte, Protocol No. 99473118.2.0000.5292. Results: The participants who achieved the highest means of knowledge level were female (6.04 ± 4.47), with a partner (6.13 ± 4.49), white (6.10 ± 4.46) and received financial assistance from the government (6.72 ± 4.40). Most teenagers reported that they had already had their first sexual intercourse. Of those who continued to have sex in the last 6 months, only 31.3% used a condom. Final considerations: Adolescents have a considerable level of knowledge about the prevention of HIV/AIDS and other STIs, but their sexual practices do not follow the recommended preventive measures.